Conceptual model of a web-based traffic flow management system in an urban environment based on microservice architecture - Roskladka, Andrii; Postrelko, Yevhenii (Technologies and Engineering, 2026)
The relevance of the research arises from the growing load on urban transport infrastructure, the need for digital transformation of mobility management, and the implementation of intelligent data analytics technologies operating in real time. Such a system enables prompt responses to changes in traffic conditions, improves the efficiency of the route network, and enhances the overall quality of urban transportation services. The purpose of the study was to design the architecture of a web system that ensures the integration of data from city application programming interfaces, their automated processing, analytical interpretation, visualisation of results, and centralised configuration management. The methodological basis of the research included approaches of systems analysis, data flow modelling, the construction of entity-relationship diagrams, and the use of architectural design patterns to represent the structural and functional interaction of components. The article presented the development of a conceptual model of a web- based system for managing traffic flows in an urban environment, designed according to the principles of microservice architecture. The research outcome was the creation of a structural model of the system comprising five interrelated microservices: integration with city application programming interfaces (Node.js), data processing and aggregation (Python, Redis Streams), an analytical module with machine learning algorithms (Scikit-learn), a visualisation module (React, Mapbox, Chart.js), and a service for access control and configuration management. The paper provided a detailed description of their interaction logic, scaling mechanisms, and reliability assurance. The practical value of the study lied in the development of a universal architectural framework for implementing systems of analytics and monitoring of urban transport, which may serve as a prototype for intelligent mobility management platforms within the Smart City concept.